Respuesta :

x=-3

-3*6 +4=-14
4*-3 -2=-14

Hope that helps!
Subtract 4x+4
  2x = -6
Divide by 2
  x = -3

_____
When you don't know where to start on a linear equation, you can just subtract the expression on one side so you have an expression equal to zero. Here (below), we choose to subtract (4x -2), the expression on the right, because 4x has a smaller coefficient of x than does 6x. The result will be an x-term with a positive coefficient. (Planning ahead.)
  (6x +4) -(4x -2) = 0
  2x +6 = 0
Now, you have a variable term and a constant term. In either order, subtract the constant term and divide by the coefficient of the variable term.
  2x = -6
  x = -3
or
  x +3 = 0
  x = -3

_____
Remember always and truly: whatever you do to one side of the equation, you must also do to the other side.

Here, for example, when I say "subtract such-and-such", it means "subtract such-and-such from both sides of the equation."

There are folks who will tell you "move such-and-such to the other side and change its sign." Don't even begin to think that way. If you already have been told that, immediately drop that habit of thought.

WHATEVER YOU DO TO ONE SIDE OF THE EQUATION, YOU MUST ALSO DO TO THE OTHER SIDE. This rule is the entire basis for solving algebraic equations.